Pengaruh Work Life Balance Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan PT China Comservice Indonesia Di Jakarta Pusat - Daniel Rian Tricahyo; Ibnu Sina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of Work Life Balance and Leadership Style on Employe Performance at PT. China Comservice Indonesia in Jakarta both partially and simultaneously. This study uses a quantitative method with an associative ap-proach. The population and sample size consisted of 53 employes who are employes of PT. China Comservice Indonesia in Jakarta. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, regression analysis, correla-tion coefficients, determination coefficients, and hypothesis testing. And it was found that Work Life Balance has a positive and significant effect on employe performance with the regression equation Y = 12.516 + 0.715X1. The hypothesis test yielded a t-value of (3.820 > 2.00856). Therefore, H0 is rejected and H1 is accepted. Leadership Style has a positive and significant effect on employe performance with the regression equation Y = 17.812 + 0.617X2. The hypothesis test yielded a t-value of (7.350 > 2.00856), thus H0 is rejected and H2 is accepted. Work Life Balance and Leadership Style simultaneously have a positive and significant effect on employe performance with the regression equation Y = 6.077 + 0.366X1 + 0.677X2. The hypothesis test yielded a calculated F-value > table F-value (32.458 > 3.18) followed by a signifi-cance value of 0.000 < 0.05. Therefore, H0 is rejected and H3 is accepted. From the above results, the recommendations are to reorganize job desk assignments and work-load, leaders need to be more open to receiving criticism, and to improve the quality of training effectively to enhance employe performance at PT. CCSI in Jakarta